Slag-steel slag based geopolymer concrete and preparation method thereof
By using slag and steel slag in geopolymer concrete, combined with alkali exciter and retarder of solid alkali and water glass, the problem of poor mechanical properties of geopolymer concrete at room temperature is solved, and the effects of strength improvement, porosity reduction and radiation safety are achieved.
Patent Information
- Application Number
- CN202510182004.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing geopolymer concrete has poor mechanical properties at room temperature and requires high-temperature curing to improve strength. However, high-temperature curing increases energy consumption and may damage the granular structure of geopolymers, resulting in an increase in porosity. At the same time, coal-fired furnace slag has an enrichment effect on radionuclides, which may lead to radiation exceeding the standard.
Slag and steel slag are used as gel materials, and their proportions are controlled to moderate hydration reaction speed. A mixture of solid alkali and water glass is used as alkali exciter. The modulus of water glass is adjusted to control the hydration reaction, and a retarder is added to extend the initial settling time.
The mechanical properties of ground polymer concrete at room temperature are improved, the porosity and energy consumption are reduced, the radiation exceeds the standard, and the durability and density of concrete are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of geopolymer concrete, and in particular to a slag-steel slag-based geopolymer concrete and a preparation method thereof. Background Art
[0002] Geopolymer is an inorganic silica-alumina gel material mainly composed of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron, which is generated by stimulating strong alkaline solution from bulk solid waste, mineral waste and construction waste. Geopolymer has excellent performance in many aspects, such as high strength, short setting time and excellent high temperature resistance. In addition, due to the absence of calcium carbonate decomposition (producing CO 2 ) and high-temperature firing process of cement clinker, the carbon emission of geopolymer concrete production process is significantly lower than that of silicate cement concrete.
[0003] According to the existing technology, geopolymers usually need high temperature (50-100℃) curing to obtain higher early strength and mechanical properties better than concrete. For example, the literature (X.Guo, J.Yang, Intrinsic properties and micro-crack characteristics of ultra-high toughness fly ash / steel slag based geopolymer, Construction and Building Materials.230(2020)) compared the 7d compressive strength of fly ash-steel slag based geopolymers cured at 20℃ and 60℃. The results show that increasing the curing temperature is conducive to the development of strength, but it will reduce the strain characteristics and structural density. The disadvantages of high temperature curing are: it increases the energy consumption of the geopolymer preparation process and limits the application of geopolymers in cast-in-place structures. At the same time, long-term high temperature curing will destroy the granular structure of the geopolymer and cause a large amount of water in the geopolymer matrix to evaporate, thereby causing an increase in porosity.
[0004] Patent CN116730668A provides a geopolymer using coal-fired furnace slag and blast furnace slag as gel materials, and using a low-modulus alkaline activator. Through the interaction of the three, the early hydration reaction can be slowed down, the early coagulation time can be extended, and shrinkage and cracking can be avoided, forming a geopolymer with low porosity and high density. It not only has good mechanical strength and stability, but also has excellent resistance to chloride ion corrosion. At the same time, since the modulus of water glass in the activator is relatively low (1.0-1.3), alkali efflorescence and shrinkage of the geopolymer can be avoided. By adjusting the amount of activator added to form a low-concentration alkaline solution, a denser internal structure is obtained while ensuring that the gel material fully reacts, avoiding the subsequent alkali efflorescence.
[0005] However, studies have shown that (Wulin, Deng Yuequan, Sun Ting, et al. Study on radon pollution in coal slag bricks using steel slag [J]. Concrete and Cement Products, 2015, (10): 86-89.) 226 Radioactive nuclides such as Ra have an enrichment effect, which can easily cause the radiation of coal slag building materials to exceed the standard, resulting in radioactive pollution indoors. In addition, the CaO content of coal-fired slag is low, and for geopolymers, the activation reaction during alkali activation is weak, and the product strength is also low. Therefore, the existing technology needs to be improved. Summary of the invention
[0006] The object of the present invention is to provide a slag-steel slag-based geopolymer concrete and a preparation method thereof, so as to solve the above-mentioned problems existing in the existing geopolymer concrete.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The invention provides a slag-steel slag-based polymer concrete, comprising the following raw materials in parts by mass: 345-460 parts of slag, 230-345 parts of steel slag, 1380 parts of standard sand, 176-243 parts of alkali activator, 140-184 parts of water, and 1-10 parts of retarder.
[0009] Preferably, in the above-mentioned slag-steel slag-based polymer concrete, the alkali activator is a mixture of solid alkali and water glass; the modulus of the water glass after the solid alkali and water glass are mixed is 1.1-1.4.
[0010] Preferably, in the above-mentioned slag-steel slag-based polymer concrete, the mass ratio of the total mass of the slag and steel slag to the mass ratio of the water glass in the alkali activator is 1:0.2-0.31.
[0011] Preferably, in the above-mentioned slag-steel slag-based polymer concrete, in the alkali activator, the mass fraction of water glass is 144-211 parts, and the mass fraction of solid alkali is 32 parts.
[0012] Preferably, in the above-mentioned slag-steel slag-based polymer concrete, the retarder is barium chloride.
[0013] Preferably, in the above-mentioned slag-steel slag-based polymer concrete, the chemical components of the slag, by mass fraction, the first five digits include 34-35% SiO 2 , 33~35%CaO, 17~18%Al 2 O 3 , 6~7%MgO, 1~3%SO 3 .
[0014] Preferably, in the above-mentioned slag-steel slag-based polymer concrete, the chemical components of the steel slag, by mass fraction, the first five components include 26-27% CaO, 22-23% SiO 2 , 22~23%Fe 2 O 3 , 6~7%Al 2 O 3 , 5~6%MgO.
[0015] The present invention also provides a method for preparing slag-steel slag-based polymer concrete, comprising the following steps:
[0016] Mix steel slag, slag, standard sand and retarder to obtain dry material; mix the dry material, alkali activator and water, pour into a mold, first cure indoors, and then cure at room temperature in a standard curing box to the specified age after demoulding.
[0017] Preferably, in the above-mentioned method for preparing slag-steel slag-based polymer concrete, the indoor curing time is 24 hours.
[0018] Preferably, in the above-mentioned method for preparing slag-steel slag-based polymer concrete, the conditions for normal temperature curing in the standard curing box are: temperature of 22-24° C.; humidity ≥95%.
[0019] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention uses slag and steel slag as gel materials, controls the ratio of slag and steel slag in the gel materials, and makes the hydration reaction speed in the early stage moderate, and the early reaction will not be too intense. This can make the geopolymer maintain good mechanical properties in the early stage, and will not have many pores and cracks. At the same time, it can also prolong the hydration reaction, improve the subsequent mechanical strength and durability, reduce the porosity, and improve the mechanical properties and structural density of the geopolymer concrete under normal temperature curing conditions.
[0021] (2) The present invention further controls the early hydration reaction speed by changing the modulus of water glass (alkali activator), thereby improving the early strength. When the water glass modulus changes, the mechanical properties of the geopolymer are different. The appropriate water glass modulus can avoid the problems of alkali efflorescence and severe shrinkage of the geopolymer, and can also make the gel material react fully to obtain a denser internal structure to improve its mechanical strength. At the same time, by adjusting the amount of alkali activator added to form a low-concentration alkaline solution, the cost can be reduced.
[0022] (3) The present invention also adds a retarder, which prolongs the time to reach initial setting to a certain extent, can effectively prevent the flash setting phenomenon of the geopolymer and obtain a geopolymer concrete with excellent mechanical properties and good construction and workability. DETAILED DESCRIPTION
[0023] The invention provides a slag-steel slag-based polymer concrete, comprising the following raw materials in parts by mass: 345-460 parts of slag, 230-345 parts of steel slag, 1380 parts of standard sand, 176-243 parts of alkali activator, 140-184 parts of water, and 1-10 parts of retarder.
[0024] In the present invention, different ratios of slag and steel slag will directly affect the mechanical strength of the geopolymer. When the ratio of steel slag is too high, the compressive strength of the geopolymer will decrease. The ratio of the present invention can effectively extend the early coagulation time of the geopolymer, slow down the violent hydration reaction of the test block in the early stage, and improve its internal structure. In addition, through a certain period of maintenance, its strength will continue to increase.
[0025] In the present invention, the chemical composition of the slag is calculated by mass fraction, and the first five digits include 34-35% SiO 2 , 33~35%CaO, 17~18%Al 2 O 3 , 6~7%MgO, 1~3%SO 3 The chemical composition of the slag used in the embodiment of the present invention includes: 34.5% SiO 2 , 34%CaO, 17.7%Al 2 O 3 , 6.01% MgO, 1.64% SO 3 .
[0026] In the present invention, the chemical composition of the steel slag is calculated by mass fraction, and the first five components include 26-27% CaO, 22-23% SiO 2 , 22~23%Fe 2 O 3 , 6~7%Al 2 O 3 , 5-6% MgO. The chemical composition of the steel slag used in the embodiment of the present invention includes: 26.85% CaO, 22.6% SiO 2 , 22.3%Fe 2 O 3 , 6.07%Al 2 O 3 , 5.63%MgO.
[0027] In the present invention, due to the high CaO content in slag, when slag is used alone as a gel material, a large amount of calcium ions released in the early stage of the hydration reaction will combine with silicon ions to form a large amount of calcium silicate hydrate (CSH gel). Subsequently, due to the rapid formation speed of CSH gel, the bonding effect of the gel material will be seriously affected, and more pores and cracks will appear inside it, affecting the overall density and strength. However, the CaO content in steel slag is relatively low. The geopolymer made by using steel slag alone as a gel material has a weak hydration effect and generates less CSH gel, which will lead to poor early mechanical properties of the test block under normal temperature curing conditions, and high temperature and long-term curing are required to fully hydrate the interior.
[0028] In the present invention, the alkali activator is preferably a mixture of solid alkali and water glass; the modulus of the water glass after the solid alkali and water glass are mixed is preferably 1.1 to 1.4, more preferably 1.2 to 1.4, and more preferably 1.4.
[0029] In the present invention, in the alkali activator, the mass fraction of water glass is preferably 144 to 211 parts, more preferably 200 to 211 parts, and more preferably 211 parts; the mass fraction of solid alkali is preferably 32 parts.
[0030] In the present invention, the initial modulus of the water glass is preferably 3.3, wherein the mass fraction of silicon dioxide is preferably 27.3%, and the mass fraction of sodium oxide is preferably 8.54%. The present invention adjusts the water glass modulus to the required 1.1-1.4 by adding solid alkali.
[0031] In the present invention, the solid base is preferably sodium hydroxide.
[0032] In the present invention, the mass ratio of the total mass of the slag and steel slag to the mass ratio of the water glass in the alkali activator is preferably 1:0.2-0.31, more preferably 1:0.25-0.31, and even more preferably 1:0.31.
[0033] In the present invention, the retarder is preferably barium chloride.
[0034] The present invention also provides a method for preparing slag-steel slag-based polymer concrete, comprising the following steps:
[0035] Mix steel slag, slag, standard sand and retarder to obtain dry material; mix the dry material, alkali activator and water, pour into a mold, first cure indoors, and then cure at room temperature in a standard curing box to the specified age after demoulding.
[0036] In the present invention, the indoor curing time is preferably 24 hours.
[0037] In the present invention, the conditions for normal temperature curing in the standard curing box are: the temperature is preferably 22-24°C, more preferably 23-24°C, and more preferably 23°C; the humidity is preferably ≥95%, more preferably ≥97%, and more preferably 98%.
[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] The present embodiment provides a slag-steel slag-based polymer concrete, comprising the following raw materials in parts by mass: 345 parts of slag, 345 parts of steel slag, 1380 parts of standard sand, 211 parts of water glass, 32 parts of sodium hydroxide, 140 parts of additional water, and 6 parts of barium chloride; wherein the modulus of the water glass in the presence of sodium hydroxide is 1.4.
[0041] The method for preparing the slag-steel slag-based polymer concrete comprises the following steps:
[0042] (1) Mixing sodium hydroxide and additional water to prepare an alkaline solution, and letting it stand for 24 hours until it reaches room temperature;
[0043] (2) adding steel slag, slag, standard sand and barium chloride into a mixer and mixing for 5 minutes to obtain dry materials;
[0044] (3) adding alkaline solution and water glass to the dry material and continuing stirring for 3 minutes to obtain a mixture;
[0045] (4) Pour the mixture into a 150 mm standard sample box coated with lubricating oil, vibrate with a tamping rod while pouring, and vibrate on a vibration table for 60 seconds after pouring to allow the bubbles to fully dissipate;
[0046] (5) After 24 hours of indoor curing, demould and place in a standard curing box with a temperature of 23°C and a humidity of not less than 95% for 28 days.
[0047] The slag-steel slag-based polymer concrete prepared in Example 1 was tested for compressive strength and porosity. The method for compressive strength testing is as follows: referring to the requirements for experimental samples in the Standard for Engineering Rock Test Methods, the uniaxial compression sample was processed into a cylindrical sample with a diameter of 50 mm, a height of 100 mm, a height-to-diameter ratio of 2, and an end surface flatness tolerance and a verticality tolerance not exceeding 0.05 mm, and the compressive strength test was performed using a GCTS RTR-1500 high-temperature and high-pressure rock triaxial strain gauge in accordance with the Standard for Engineering Rock Test Methods (GBT50266-2013). The method for porosity testing is as follows: a standard disc sample with a diameter of 50 mm and a height of 25 mm was subjected to a 24-hour negative pressure vacuum saturation treatment, the sample surface moisture was wiped off after removal, and a nuclear magnetic resonance experiment was performed using a MesoMR12-060H-I nuclear magnetic resonance analysis and imaging system. After testing, the results of three 28d compressive strength tests were 64.9MPa, 73.6MPa, and 78.8MPa respectively, and the average value of 72.4MPa was taken as the final result. The porosity obtained by NMR experiment was 8.16%.
[0048] Example 2
[0049] The present embodiment provides a slag-steel slag-based polymer concrete, comprising the following raw materials in parts by mass: 460 parts of slag, 230 parts of steel slag, 1380 parts of standard sand, 144 parts of water glass, 32 parts of sodium hydroxide, 184 parts of additional water, and 6 parts of barium chloride; wherein the modulus of the water glass in the presence of sodium hydroxide is 1.1.
[0050] The method for preparing the slag-steel slag-based polymer concrete comprises the following steps:
[0051] (1) Mixing sodium hydroxide and additional water to prepare an alkaline solution, and letting it stand for 24 hours until it reaches room temperature;
[0052] (2) adding steel slag, slag, standard sand and barium chloride into a mixer and mixing for 5 minutes to obtain dry materials;
[0053] (3) adding alkaline solution and water glass to the dry material and continuing stirring for 3 minutes to obtain a mixture;
[0054] (4) Pour the mixture into a 150 mm standard sample box coated with lubricating oil, vibrate with a tamping rod while pouring, and vibrate on a vibration table for 60 seconds after pouring to allow the bubbles to fully dissipate;
[0055] (5) After 24 hours of indoor curing, demould and place in a standard curing box with a temperature of 23°C and a humidity of not less than 95% for 28 days.
[0056] According to the detection method of Example 1, the results of three 28d compressive strength tests of the slag-steel slag-based polymer concrete prepared in Example 2 were 60.2 MPa, 61.2 MPa, and 65.6 MPa, respectively, and the average value of 62.3 MPa was taken as the final result. The porosity obtained by the NMR experiment was 8.64%.
[0057] Example 3
[0058] The present embodiment provides a slag-steel slag-based polymer concrete, comprising the following raw materials in parts by mass: 345 parts of slag, 345 parts of steel slag, 1380 parts of standard sand, 144 parts of water glass, 32 parts of sodium hydroxide, 184 parts of additional water, and 6 parts of barium chloride; wherein the modulus of the water glass in the presence of sodium hydroxide is 1.1.
[0059] The method for preparing the slag-steel slag-based polymer concrete comprises the following steps:
[0060] (1) Mixing sodium hydroxide and additional water to prepare an alkaline solution, and letting it stand for 24 hours until it reaches room temperature;
[0061] (2) adding steel slag, slag, standard sand and barium chloride into a mixer and mixing for 5 minutes to obtain dry materials;
[0062] (3) adding alkaline solution and water glass to the dry material and continuing stirring for 3 minutes to obtain a mixture;
[0063] (4) Pour the mixture into a 150 mm standard sample box coated with lubricating oil, vibrate with a tamping rod while pouring, and vibrate on a vibration table for 60 seconds after pouring to allow the bubbles to fully dissipate;
[0064] (5) After 24 hours of indoor curing, demould and place in a standard curing box with a temperature of 23°C and a humidity of not less than 95% for 28 days.
[0065] According to the detection method of Example 1, the results of three 28d compressive strength tests of the slag-steel slag-based polymer concrete prepared in Example 3 were 57.7 MPa, 59.8 MPa, and 62.4 MPa, respectively. The average value of 59.9 MPa was taken as the final result. The porosity obtained by the NMR experiment was 9.49%.
[0066] Comparative Example 1
[0067] This comparative example provides a slag-steel slag based polymer concrete, which is specifically referred to in Example 1, except that the amount of water glass is 92 parts, the amount of additional water is 217 parts, and the modulus of the water glass in the presence of sodium hydroxide is 0.8.
[0068] According to the detection method of Example 1, the results of three 28d compressive strength tests of the slag-steel slag-based polymer concrete prepared in Comparative Example 1 were 26.9 MPa, 28.8 MPa, and 38.5 MPa, respectively, and the average value of 31.4 MPa was taken as the final result. The porosity obtained by the NMR experiment was 12.42%.
[0069] Comparative Example 2
[0070] This comparative example provides a slag-steel slag based polymer concrete, which is specifically referred to in Example 2, except that the steel slag is 460 parts and the slag is 230 parts.
[0071] According to the detection method of Example 1, the results of three 28d compressive strength tests of the slag-steel slag-based polymer concrete prepared in Comparative Example 2 were 30.7 MPa, 35.1 MPa, and 46.6 MPa, respectively, and the average value of 37.5 MPa was taken as the final result. The porosity obtained by the NMR experiment was 11.62%.
[0072] In summary, the key to the present invention is to select slag and steel slag as gel materials, adjust the mass ratio of the two and the water glass modulus of the alkali activator, and add a certain amount of retarder. The geopolymer concrete prepared by the present invention has an average compressive strength of 72.4 MPa at 28 days and a porosity as low as 8.16%. It has good mechanical properties and pore structure, utilizes solid waste and can meet the needs of the building materials field, and has obvious technical advantages.
[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A slag-steel slag based polymer concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 345-460 parts of slag, 230-345 parts of steel slag, 1380 parts of standard sand, 176-243 parts of alkali activator, 140-184 parts of water and 1-10 parts of retarder.
2. The slag-steel slag based polymer concrete according to claim 1, characterized in that: The alkali activator is a mixture of solid alkali and water glass; after the solid alkali and water glass are mixed, the modulus of the water glass is 1.1-1.
4.
3. The slag-steel slag based polymer concrete according to claim 2, characterized in that: The mass ratio of the total mass of the slag and the steel slag to the mass ratio of the water glass in the alkali activator is 1:0.2-0.
31.
4. The slag-steel slag based polymer concrete according to claim 3, characterized in that: In the alkali activator, the mass fraction of water glass is 144 to 211 parts, and the mass fraction of solid alkali is 32 parts.
5. The slag-steel slag based polymer concrete according to claim 1 or 3, characterized in that: The retarder is barium chloride.
6. The slag-steel slag based polymer concrete according to claim 1, characterized in that: The chemical components of the slag are calculated by mass fraction, and the first five components include 34-35% SiO2, 33-35% CaO, 17-18% Al2O3, 6-7% MgO, and 1-3% SO3.
7. The slag-steel slag based polymer concrete according to claim 6, characterized in that: The chemical components of the steel slag are calculated by mass fraction, and the first five components include 26-27% CaO, 22-23% SiO2, 22-23% Fe2O3, 6-7% Al2O3, and 5-6% MgO.
8. The method for preparing slag-steel slag based polymer concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mix steel slag, slag, standard sand and retarder to obtain dry material; mix the dry material, alkali activator and water, pour into a mold, first cure indoors, and then cure at room temperature in a standard curing box to the specified age after demoulding.
9. The method for preparing slag-steel slag based polymer concrete according to claim 8, characterized in that: The indoor curing time is 24 hours.
10. The method for preparing slag-steel slag based polymer concrete according to claim 9, characterized in that: The conditions for normal temperature curing in the standard curing box are: temperature of 22-24° C.; humidity ≥95%.
Citation Information
Patent Citations
Geopolymer-based steel slag dry-mixed mortar binder
CN104150793A
3D printing alkali-fast cement concrete and preparation method thereof
CN108178567A
Slag alkali cement and its producing method
CN1094382A
High-strength and high-toughness steel slag-based cementing material and preparation method thereof
CN117550867A
Preparation of homogenized frozen gravel and dynamic testing method under low temperature environment
CN118758696A